Overcoming contradictions in models of key competencies of the system of educational standards and KPI for fitness managers - Sazonov I.Yu.; Polozov A.A.; Maltseva N.A.; Petukhova M.E. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify a set of key competencies for fitness club managers, based on the practice of their work, in order to include them in educational programs of universities. Methods and structure of the study. An analysis of normative and methodological literature devoted to the topic of determining and assessing the competencies of specialists employed in the fitness industry was carried out. Results and conclusions. During the scientific work, professional competencies related to management, marketing, sales, personnel, and law were identified. To normalize, it is necessary to formulate a separate standard for a fitness club manager and, depending on the success of mastery, indicate the specialization in the diploma (manager-manager, manager-marketing, etc.). The relative importance of each aspect of these areas and the profit created by the manager was determined from the regression equation based on the results of testing 19 managers (R^2 = 0.97). It is recommended to match the time spent studying an aspect to its level of significance.